2020
DOI: 10.1016/j.conbuildmat.2020.120789
|View full text |Cite
|
Sign up to set email alerts
|

Impact of water on peak and residual shear strength parameters and triaxial deformability of high-porosity building calcarenite stones: Interconnection with their physical and petrological characteristics

Abstract: Several studies have found that water can cause substantial reductions of mechanical properties of building stones such as unconfined compressive strength, tangent Young´s modulus or tensile strength. However, the influence of water content on shear strength parameters, triaxial compressive strength and modulus of elasticity under different confining pressures has been scarcely examined. For this reason, the present paper assesses the impact of water on peak and residual compressive strength and tangent Young´… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 68 publications
(97 reference statements)
1
7
0
Order By: Relevance
“…Research reveals that water content can play a key role in the determination of UCS and the deformational features of the intact rock, even for small variations in the moisture content due to changes in the relative humidity of the air [44,45]. Natural moisture in rocks is also related to spalling events at temperatures lower than 200º C [7][8][9].…”
Section: Heating and Cooling Proceduresmentioning
confidence: 99%
“…Research reveals that water content can play a key role in the determination of UCS and the deformational features of the intact rock, even for small variations in the moisture content due to changes in the relative humidity of the air [44,45]. Natural moisture in rocks is also related to spalling events at temperatures lower than 200º C [7][8][9].…”
Section: Heating and Cooling Proceduresmentioning
confidence: 99%
“…The petrological characteristics and physico-mecanical properties of these geomaterials under compressive conditions have been extensively analysed by Rabat et al (2020c) (Fig. 2).…”
Section: Used Rocks and Specimen Preparationmentioning
confidence: 99%
“…They have demonstrated that uniaxial compressive strength (UCS), compressive Young's modulus (E c ) and shear strength parameters of sedimentary rocks can be significantly reduced after their full and partial water saturation (e.g. Hawkins and McConnell, 1992;Vásárhelyi, 2005;Erguler and Ulusay, 2009;Shakoor and Barefield, 2009;Kim and Changani, 2016;Rabat et al, 2020aRabat et al, , 2020bRabat et al, , 2020cRabat et al, , 2021. However, the mechanical response of these geomaterials under tensile stress and its water-induced variation have been poorly analysed due to the difficulties in tensile testing (Briševac et al, 2015;Hashiba and Fukui, 2015;Okubo and Fukui, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Porous structures are exposed to different environmental factors (relative humidity and water permeability) throughout their lifetime and cracks can occur as a result of the deterioration of intergranular bonds in the rock under the effect of water pressure. As a result, the mechanical properties of the rocks decreases and their strength decreases in time [35][36][37][38].…”
Section: Pore Size Distribution (Mip) Of Travertinesmentioning
confidence: 99%